Effect of obesity on telomere length: Systematic review and meta‐analysis. (26th September 2015) - Mundstock, Eduardo; Sarria, Edgar E.; Zatti, Helen; Mattos Louzada, Fernanda; Kich Grun, Lucas; Herbert Jones, Marcus; Guma, Fátima T.C.R.; Mazzola (in Memoriam), João; Epifanio, Matias; Stein, Renato T.; Barbé‐Tuana, Florencia M.; Mattiello, Rita
Abstract : Objective: The main objective of this systematic review is to assess the effects of obesity on telomere length. Methods: The following databases were searched: MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), LILACS, SPORTdiscus, and Web of Science from inception to August 2014. The search was performed using the following combinations of terms: telomere AND "overweight" OR "obesity" OR "adiposity, " without language restriction. Results: Sixty‐three original studies were included in this systematic review, comprising 119, 439 subjects. Thirty‐nine studies showed either weak or moderate correlation between obesity and telomere length; however, they showed an important heterogeneity. Conclusions: There is a tendency toward demonstrating negative correlation between obesity and telomere length. The selected studies showed weak to moderate correlation for the main search, and there was an important heterogeneity. For this reason, the causal relationship of obesity and telomere length remains open. Additional controlled longitudinal studies are needed to investigate this issue.